(untitled) (One Health & Risk Management, 2021)
Introduction. Globally, the activities of healthcare workers are associated with exposure to countless occupational hazards, including biological, chemical, physical and psychological hazards. In the Republic of Moldova, prehospital emergency medical care services are organized as to ensure the availability, efficiency and quality of medical care provided to the population, though, from a hygienic point of view, some obstacles are created to control working conditions, employee morbidity, which have not been studied and improved for decades. Material and methods. A meta-analysis of studies on the impact of occupational risk factors on Prehospital Care Emergency Medical Services (PCEMS) workers was conducted. Statistics from the database on „Evidence of infection with the COVID-19 virus in the Republic of Moldova” during the coronavirus pandemic period were analyzed and systemized. Results. The reviewed literature emphasizes that emergency healthcare workers are constantly facing a number of work-related hazards, such as contact with sick people, responsibility for the health and life of the patient, night and round-the-clock service, unpredictable atmosphere, sometimes long-distance travel, as well as intellectual and psycho-emotional stressful situations. It was also confirmed that occupational risk factors have a negative impact not only on health, but also on the quality of medical care provided to the population. Statistical data analysis indicated that, in Republic of Moldova, a total of 13,895 medical workers were infected with the COVID-19 virus during 20.07.20-07.04.21, of which 135 cases (0.9%) were fatal. Among PCEMS workers 782 COVID-19 cases were registered (5.6% of the total number of infected medical workers), including 5 people who died (3.7% of 135 deaths). At the same time, data analysis of COVID-19 infection among PCEMS, by geographical distribution, revealed the dominance in certain regions of the country: Chisinau – 243 infected medical staff, Cahul – 34 people, Balti – 30 infected workers, Causeni and Orhei – 28 cases per each. As regarding the age distribution of the infection cases, the most affected age group among PCEMS workers were aged between 49 to 58 years old – 239 registered cases, then 196 infected workers aged 39 – 48 years and 119 cases were included in the group of people aged 59-68 years old. However, a significant number of cases were also registered in young workers: 117 cases were aged between 29-38 years, 85 cases – aged 19-28 etc. Currently, the PCEMS workers face physical and emotional exhaustion, which can lead to medical errors, lack of empathy in patient care, decreased productivity and family problems. Conclusions. Due to the stress, unpredictability and often life-threatening nature of the tasks that PECMS healthcare workers face on a daily basis the quality of working life has become an inevitable challege and one of the stringent problems of society as a whole. In addition, given the work-related hazards and current conditions caused by the pandemic, work conditions and quality of life, there is a more urgent need to analyze activities in this field and to improve the overall well-being and quality of life of workers.